Effect of cultivars and weed management practices on productivity, profitability and energetics of dry direct-seeded rice - K, Pooja; P, Saravanane; V, Sridevi; S, Nadaradjan; S, Vijayakumar (ORYZA-An International Journal of Rice, 2021)
A field experiment was conducted from September 2019 to January 2020 (thaladi season) at Pandit Jawaharlal Nehru College of Agriculture and Research Institute, Karaikal, Puducherry to study the effect of cultivars and weed management practices on productivity, profitability and energetics of dry direct-seeded rice (DDSR). The experiment was laid out in a split-plot design (SPD) with 15 treatment combinations and replicated thrice. Cultivars (ADT 46, CO 52 and improved white ponni) were assigned to main plots and 5 weed management practices viz. application of pendimethalin @ 1 kg a.i ha-1 as pre-emergence (PE); bispyribac-sodium @ 0.02 kg a.i ha-1 as post-emergence (POE) at 20 DAS; pendimethalin @ 1 kg a.i ha-1 followed by (fb) bispyribac-sodium @ 0.02 kg a.i ha-1; hand weeding (HW) twice at 20 and 40 DAS and weedy check were assigned to sub-plots. Results have shown that cultivars ‘ADT 46’ was the most promising cultivar for DDSR situation since it recorded the highest grain yield (3.76 t ha-1), energy use efficiency (4.43), energy productivity (0.3 kg MJ-1), net returns (₹43.74 × 103 ha-1) and benefit: cost ratio (1.52). Among the weed management practices, sequential application of pendimethalin fb bispyribac-sodium found superior over other treatments in terms of grain yield (3.73 t ha-1), energy use efficiency (4.35), energy productivity (0.3 kg MJ-1), net returns (₹42.27× 103 ha-1) and benefit: cost ratio (1.43). Thus, cultivation of ‘ADT 46’ integrated with sequential application of pendimethalin fb bispyribac-sodium could be recommended for DDSR under coastal deltaic ecosystem of south India.